ANALISIS PROTEIN PILLI Salmonella typhi lsolat RS. Kariadi Semarang DENGAN ELEKTROFORESIS SDS-PAGE - Sri Darmawati; Ratih Haribi (JURNAL LITBANG, 2005)
Background : Salmonella typhi is bacteria which causes typhoid fever. Typhoid fever is severally serious, infectious decease and is endemic decease in Indonesia with relatively high frequency rate around 358-810/100.000 people each year This decease is usually spreading along with many kinds of decease which also have relatively high mortality rate, that is 1-5% of the sufferers (Punjabi, NH. , 2 004) . The infection process of bacteria into human body is signified with bacteria Cell adhering in mucosa intestinal surface. Pilli is structured by pilli protein consisting of Several sub units of pilli protein Objective: conducting pilli protein Salmonella typhi isolate Kariadi Hospital Semarang Analysis through electrophoreses SDS-PAGE, so that take amount of sub unit of pilli protein with each its molecule weight can be found out. Method : This research is conducted through three stages; firstly, bacteria cultivation with Biphasic media (BHI Agar and broth BHI ); secondly, pilli isolation with Ehara method (/956); Thirdly, sub unit of pilli protein separation with I 2% SDS-PAGE based on Lemmli method (1970). Result: There are four major sub units of protein in pilli, that is, 36kDa; 26,5 kDa; 22,2kDa; 18,6lrDq and there are also four minor sub units of protein pilli, that is, 116 kDa; 62,3kDa;45kDa;20,9kDa,andseveral other minor sub units of protein with every thin band. Keywords : Salmonella and Electrophoresis